Tanaidacean (Crustacea : Peracarida) fauna from chemically reduced habitats - the lucky strike hydrothermal vent system, mid-atlantic ridge - Larsen, K
The tanaidacean fauna from the hydrothermal vents in the Lucky Strike Field on the Mid-Atlantic Ridge is examined. The material reveals species belonging to the genera Agathotanais, Apseudes, Leviapseudes, Sphyrapus, Armaturatanais, Leptognathiella, Mesotanais, Pseudotanais and Typhlotanais. One new typhlotanaid genus, Obesutanais, and five new species, Armaturatanais atlanticus, Obesutanais sigridae, Mesotanais styxis, Leptognathiella fragilis, and Typhlotanais incognitus, are described.